(untitled) (Bioagro, 2021)
The rambutan fruit (Nephelium lappaceum L.) is exotic, non-traditional and very attractive in international markets; however, currently there is little information on anatomical and morphological aspects. Therefore, the objective of this study is to describe the anatomy of floral initiation and differentiation, development of gametophytes, of the aril and type of the fruit of N. lappaceum. A longitudinal design was implemented that comprises in the detection of anatomical changes of the vegetative buds towards the reproductive ones; development of pistillate flowers, as well as the ovary and ovule of the hermaphrodite flower, towards the fruit and seed. The floral initiation was presented after 41 days of pre-anthesis. The stamen has an anther with two thecae, the anthers are indehiscent and have epidermis, the endothecium develops fibrillar thickenings, it has binucleate cells and the tapetum is secretory. A locule per theca appeared with triporate pollen grains. Microsporogenesis developed normally, division of mother cells of the microspores was simultaneous and the tetrads of the microspores, with tetrahedral arrangement, were enclosed by the tapetum, which is quite thin. The gynoecium shows a bicarpellary or tricarpellary ovary. Each locule contains a campylotropous, bitegmic and crassinucellate ovule; the megagametophyte is of polygonum type. The fruit reached its maximum size, weight, and color 125 days after anthesis. It is dry, indehiscent, monospermo; it is derived from a carpel and is a schizocarpic nut.